Determine Good University Governance In Sustainable Competitive Competition At State Universities In Surabaya - Famia Septa Dinda Alfia; Indrawati Yuhertiana; Rida Perwita Sari (Green Publisher Indonesia, 2024)
This research aims to test the influence of Reputation, Legitimacy, Transparency on Good University Governance. In this research, reputation is proxied by performance, innovation, social responsibility, service, governance and workplace climate. Legitimacy is proxied by pragmatic legitimacy, moral legitimacy and cognitive legitimacy. Transparency is proxied by openness, clarity, open access and availability. Good University Governance proxied by independence, accountability, responsibility and fairness. The research method used in this research is a quantitative approach. The data used in this research came from the results of a questionnaire from undergraduate accounting students at state universities in Surabaya. This research uses the SmartPLS statistical test tool.The results of this research influence the variables reputation, legitimacy and transparency Good University Governance. The reputation variable influences good university governance at state universities in Surabaya. Legitimacy influences good university governanace at state universities in Surabaya. Transparency influences good university governance at state universities in Surabaya